Estimating overnight weight loss of corralled yearling steers in semiarid rangeland - Durante, Martin; Irisarri, Jorge Gonzalo Nicolás; Derner, Justin D.; Reeves, Justin L.; Mortenson, Matthew C.; West, Mark (2017)
A common practice for assessing livestock weight gains from grazing animals on rangelands is to confine animals overnight without feed or water to reduce variation in weight loss and percent shrink. Advances in remote sensing of vegetation, such as the Normalized Difference Vegetation Index (NDVI) provide opportunities to estimate greenness (an indicator of both the quality and quantity of the plant community) that could be used with air temperature and relative humidity as predictors of percent shrink in grazing animals. We determined percent shrink losses from crossbred yearling steers at each of four weigh dates for four consecutive years. Percent overnight shrink by yearling steers grazing semiarid rangeland was influenced positively by air temperature and NDVI values, but not relative humidity. The prediction equation we developed can provide temporal weight gain data within a grazing season without the logistical difficulties in gathering and holding animals, as well as eliminate associated animal stress from shrinking and regaining gut fill multiple times.